Penerapan Metode AHP dan Fuzzy Topsis Untuk Sistem Pendukung Keputusan Promosi Jabatan - Muhardono, Ari; Isnanto, Rizal (JSINBIS (Jurnal Sistem Informasi Bisnis), 2014)
Resources of humans is one of the assets of the organization that became the backbone of an organization in carrying out its activities and influence on the performance and progress of the organization. Systematic performance assessment and selection of employees with the best performance for the determination of a promotion is very important in strategic human resource management. But in fact the decision objectively, efficiently and effectively perform the selection of human resources is not easy, we need a model of decision-making to help solve that problem. Application of AHP and Fuzzy TOPSIS in the selection of this promotion can be provide alternative recommendations for decision-makers, so that the employee selection process can take place effectively and efficiently and to produce objective decisions. Implementation results of the study for the selection of a promotion with six criteria assessment criteria weighting the results obtained using the AHP Performance Value of 0,3509, Education Level of 0,1605, Class of 0,1005, Work period of 0,0367, The Presence of 0,0637 and the value of the competence of 0.2877. The weighting of the results was continued process of ranking the alternatives by using fuzzy TOPSIS method obtained the best results and the selected preference is for 0.8373 Â  Keywords: Performance evaluation; Promotion; AHP; Topsis; Fuzzy